2010
DOI: 10.1038/bmt.2010.308
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and clinical activity of very low-dose alemtuzumab in transplantation for acute leukemia

Abstract: The optimal dose of in vivo-administrated alemtuzumab in the allogeneic transplantation setting has not been defined. We report our experience on 37 patients with high-risk diseases, mainly acute leukemia (AML 23, ALL 10 patients), who underwent sibling (49%) or unrelated (51%) PBSCT (35 patients), and received a total dose of only 10–20 mg Campath-1H as part of the conditioning, and post-transplant CYA without MTX. The neutrophil and especially the platelet engraftment were rapid. There were only two grade II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…Chakraverty et al showed that the dose of alemtuzumab can be safely reduced to a total of 30 mg in reduced-intensity HSCT from an HLA-identical sibling donor [29]. A Greek group evaluated the efficacy of alemtuzumab at a total dose of 10-20 mg on days -2 and -1 before HSCT [30]. Even with alemtuzumab at these very low doses, there was no Grade II-IV acute GVHD after HSCT from a sibling donor.…”
Section: Discussionmentioning
confidence: 99%
“…Chakraverty et al showed that the dose of alemtuzumab can be safely reduced to a total of 30 mg in reduced-intensity HSCT from an HLA-identical sibling donor [29]. A Greek group evaluated the efficacy of alemtuzumab at a total dose of 10-20 mg on days -2 and -1 before HSCT [30]. Even with alemtuzumab at these very low doses, there was no Grade II-IV acute GVHD after HSCT from a sibling donor.…”
Section: Discussionmentioning
confidence: 99%
“…These data were confirmed by Spyridonidis et al . in a small study of 18 patients who received 10 mg alemtuzumab before sibling and matched unrelated SCT [40]. Chakraverty et al also demonstrated that dose reduction of alemtuzumab to 30 mg given on day -1 effectively prevents GvHD and is associated with more rapid lymphocyte recovery after HLA-identical sibling SCT [41].…”
Section: Pharmacology and Dosing Of Alemtuzumab In Transplant Protmentioning
confidence: 99%
“…61, 62 Alemtuzumab is lymphotoxic at concentrations > 100 ng/ml. 63 When antigen concentration is high, half-life is short because the monoclonal antibody binds to its epitope and rapidly cleared. As the antigen is depleted, clearance decreases and half-life increases.…”
Section: Pharmacokinetics/dynamics Of the Conditioning Regimenmentioning
confidence: 99%